A comparative study of traffic detection using Google map (GPS) and IoV - Alam, Mohd. Touhedul; Al Nayeem, Harun (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.